OMEGA–OSIRIS mapping of emission-line galaxies in A901/2:IV. Extinction of star formation estimators with inclination - Wolf, Christian; Weinzirl, Tim; Aragón-Salamanca, Alfonso; Gray, Meghan E.; Rodríguez del Pino, Bruno; Chies-Santos, Ana L.; Bamford, Steven P.; Böhm, Asmus; Harborne, Katherine (Oxford University Press, 2018)
We study the effect of inclination on the apparent brightness of star-forming galaxies in spectral passbands that are commonly used as star formation indicators. As diagnostics we use mass-to-light ratios in three passbands: the UV continuum at 280 nm, the Hα emission line, and the FIR 24μ band. We include a study of inclination trends in the IR/UV ratio (‘IRX’) and the IR/Hα ratio. Our sample comprises a few hundred galaxies from the region around the clusters Abell 901/902 with deep data and inclinations measured from outer discs in Hubble Space Telescope images. As a novelty, the Hα- and separately the N ii emission are measured by tunable-filter imaging and encompass galaxies in their entirety. At galaxy stellar masses above log M*/M⊙ ≳ 10 we find trends in the UV and Hα mass-to-light ratio that suggest an inclination-induced attenuation from face-on to edge-on of ∼1 mag and ∼0.7 mag in UV and Hα, respectively, implying that star formation rates of edge-on galaxies would be underestimated by ∼2.5 × in UV and ∼2 × in Hα. We find the luminosities in UV and Hα to be well correlated, but the optical depth of diffuse dust that causes inclination dependence appears to be lower for stars emitting at 280 nm than for gas clouds emitting Balmer lines. For galaxies with log M*/M⊙ ≲ 9.7, we find no measurable effect at >0.1 mag. The absence of an inclination dependence at 24μ confirms that the average galaxy is optically thin in the FIR.